Pharmacokinetics of Oral Treprostinil in Children With Pulmonary Arterial Hypertension. Issue 1 (July 2020) - Hopper, Rachel K.; Ivy, D. Dunbar; Yung, Delphine; Mullen, Mary P.; Hanna, Brian D.; Kirkpatrick, Edward; Hirsch, Russel; Austin, Eric D.; Fineman, Jeffrey; Solum, Derek; Deng, C. Q.; Feinstein, Jeffrey A.
Abstract : Abstract: As part of a clinical trial, this study examined the pharmacokinetics (PK) of oral treprostinil (TRE) in children with pulmonary arterial hypertension. The trial consisted of the following 3 cohorts: transition from parenteral (cohort 1) or inhaled (cohort 2) TRE, or de novo addition (cohort 3). Oral TRE was dosed 3 times daily. PK samples were obtained before an oral TRE dose, and at 2, 4, 6, and 8 hours thereafter. The PK parameters were calculated using noncompartmental analysis. Thirty-two children (n = 10 in cohorts 1 and 2, n = 12 in cohort 3) were enrolled; the median age was 12 years (range 7–17 years), and the median weight was 42.2 kg (range 19.3–78 kg). The median oral TRE dose for all subjects was 3.8 mg (5.9, 3.5, and 4.0 mg for cohorts 1, 2, and 3, respectively). The TRE concentration versus time profile demonstrated a peak concentration at a median of 3.8 hours with wide variability. In cohort 1, oral dosing led to higher peak (5.9 ng/mL) and lower trough (1 ng/mL) concentrations than parenteral (peak 5.4 ng/mL and trough 4.2 ng/mL), but a lower mean concentration (3.61 vs. 4.46 ng/mL), likely due to variable metabolism and noncomparable dosing. Both the area under the curve and average concentration were linearly correlated with oral TRE dose and dose normalized to body weight, but not with weight or age alone. In pediatric patients, an increased oral TRE dose or dose frequency may be required to minimize PK variability and achieve greater correlation with parenteral dosing.